A Back‐to‐Base Experience of Human Normothermic Ex Situ Liver Perfusion: Does the Chill Kill?. Issue 6 (21st May 2019) - Bral, Mariusz; Dajani, Khaled; Leon Izquierdo, Dayne; Bigam, David; Kneteman, Norman; Ceresa, Carlo D. L.; Friend, Peter J.; Shapiro, A. M. James
Abstract : Normothermic machine perfusion (NMP) has been shown to protect livers from injury between procurement and transplantation in a randomized controlled trial, where the machine was transported to and from the donor center. The aim of this study was to determine whether an alternative, more practical back‐to‐base approach after initial static cold storage would compromise beneficial outcomes. Between February 2015 and June 2018, a nonrandomized pilot study was performed at a single site. Outcomes of back‐to‐base livers (n = 26) were compared with those of grafts procured locally that underwent immediate NMP (n = 17). The primary outcome measure (safety) was defined as 30‐day patient and graft survival. A total of 46 liver grafts were perfused with NMP, of which 3 were discarded based on poor ex situ perfusion function. The 30‐day patient and graft survival in the back‐to‐base and local NMP groups were both 100% (primary outcome: safety). Despite significantly prolonged mean cold ischemia time (6 versus 3.2 hours; P = 0.001), the back‐to‐base livers demonstrated no difference in graft function, incidence of complications, or graft and patient survival. In conclusion, the back‐to‐base approach was safe, did not compromise the overall benefit of NMP, and offers a practical alternative to portable normothermic ex situ machine transport.